KONSUMSI GAS SEKTOR RUMAH TANGGA DAN INDUSTRI SERTA BAHAN BAKAR MINYAK SEBAGAI ASET SEKTOR TRANSPORTASI DITINJAU DARI KARAKTERISTIKNYA DI DAERAH ISITMEWA YOGYAKARTA - Wahyuni, Sri Wahyuni (Jurnal Bulletin, 2018)
Abstrct: Gas Consumption of Household and Industrial Sectors and Oil Fuels As Assets of the Transportation Sector Viewed from Its Characteristics in the Special Region of Yogyakarta. The characteristics of gas consumption in the household and industrial sectors as well as the fuel oil of the transportation sector in the Province of Daerah Istimewa Yogyakarta (DIY) have been carried out. This research uses data from field surveys in January 2016. Average gas consumption in DIY for household sector is 90 kg/year and industrial sector is 395.98 kg/year. The fuel consumption of the transportation sector for motorcycles is 208 liters/year and the car is 956 liters/year. 73.65% respondents of transportation sector willing to be converted to gas fuel and the remaining 26.35% not willing. Abstrak: Konsumsi Gas Sektor Rumah Tangga Dan Industri Serta Bahan Bakar Minyak Sebagai Aset Sektor Transportasi Ditinjau Dari Karakteristiknya Di Daerah Isitmewa Yogyakarta.  Telah dilakukan karakteristik konsumsi gas sektor rumah tangga dan industri serta BBM sektor transportasi di Provinsi Daerah Istimewa Yogyakarta (DIY). Penelitian ini menggunakan data survei lapangan pada bulan Januari 2016. Rata-rata konsumsi gas di DIY untuk sektor rumah tangga sebesar 90 kg/tahun dan sektor industri 395,98 kg/tahun. Konsumsi BBM sektor transportasi untuk motor sebesar 208 liter/tahun dan mobil 956 liter/tahun. 73,65% responden sektor transportasi bersedia dikonversikan ke bahan bakar gas dan sisanya 26,35% tidak bersedia.             Kata kunci: gas, bbm, rumah tangga, industri, transportasi, aset